Critical evaluation of two approaches to achieve universal health coverage in India - Sriram, Shyamkumar (International Journal Of Community Medicine And Public Health, 2018)
The WHO report on the path to Universal Health Coverage (UHC) emphasizes that every person should receive the necessary healthcare without enduring financial hardship at the time of getting care. United Nations’ Sustainable Development agenda incorporates one goal (Goal 3) that is related to health and well-being of the population and one of the specific targets of the goal is to improve financial risk protection through the achievement of universal health coverage. More than 100 countries in the world have either started their reforms towards UHC or have already achieved it and India is one of the countries trying to achieve UHC. Out of the 1.324 billion people in India, only 11% of the population has any form of health insurance coverage. Around, 42% of India’s population is Below Poverty Line (BPL). Rashtriya Swasthya Bima Yojana is a health insurance program started in 2007 that provides a wide range of healthcare services for BPL families. Rajiv Aarogyasri Community Health Insurance is a state health insurance program started in Andhra Pradesh as one of the first programs in India to provide health insurance to poor people. In India, 39 million people are being impoverished due to OOP health expenditures each year, and a quarter of these expenditures are contributed by hospitalization Out-of-pocket expenditures even after the financial protection provided by a number of health insurance programs. This review will critically evaluate the two health insurance approaches which aim to achieve UHC in India by providing health protection to the indigent.